ANALISIS TINGKAT KESEHATAN BANK MENGGUNAKAN METODE RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, AND CAPITAL (RGEC) PADA PT BANK RAKYAT INDONESIA (PERSERO) TBK - Hamid, Muhammad Syarwan; Rustam, Andi; Adil, Muhammad (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to analyze the health level of PT Bank Rakyat Indonesia (Persero) Tbk for the period 2020-2024 using the RGEC method (Risk Profile, Good Corporate Governance, Earnings, and Capital). The data used are financial reports and information related to the company. The results of the study indicate that in general, PT Bank Rakyat Indonesia (Persero) Tbk is in a very healthy condition. The Risk Profile (NPL and LDR) is classified as good, with an average NPL below 2%. Good Corporate Governance (GCG) is considered good with a score of 2. Earnings performance (ROA and NIM) is very healthy, with an average ROA of 3.50%. Capital Adequacy Ratio (CAR) also shows a very healthy condition. Overall, the bank is able to maintain stability and fulfill its obligations well.Keywords: Bank Health Level, RGEC, NPL, LDR, GCG, ROA, NIM, CAR, Bank BRI.